(untitled) (Research, Society and Development, 2023)
With the advancement of aesthetics, it is necessary to constantly evolve dental materials in search of natural mimicry. As a result, monochromatic resins emerged, bringing the famous chameleon effect capable of adapting to the colors of the walls surrounding the teeth, providing a restorative material that is pleasantly aesthetic and easy to handle, eliminating the need to select the color of the teeth and the use of different resins, thus reducing the time in the dental chair. The objective of this study was to evaluate the effectiveness of monochromatic composite resins, demonstrating their use and effectiveness in the dental office through a clinical case. Patient MJMS, 70 years old, attended the dental clinic of Universidade Tiradentes (UNIT) complaining of tooth sensitivity due to the fracture of the cervical restoration of tooth 26. The chosen treatment was restoration with the unit’s monochromatic composite, which served well clinical need, optimizing service time. Monochromatic composite resin is a great material available on the market because of its ability to mimic natural teeth, achieving a pleasant aesthetic, associated with the practicality of shorter clinical time.